2016
DOI: 10.4067/s0717-95022016000300023
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Posterior Antebrachial Cutaneous Nerve Related to the Lateral Epicondyle and Interepicondylar Line

Abstract: CHODEWARATHAM, P.; CHENTANEZ, V.; AGTHONG, A. & HUANMANOP, T.Anatomy of posterior antebrachial cutaneous nerve related to the lateral epicondyle and interepicondylar line. Int. J. Morphol., 34(3):953-957, 2016. SUMMARY:Posterior antebrachial cutaneous nerve (PACN) is a branch of radial nerve supplying the skin of posterior forearm. Data regarding its anatomy remain insufficient especially the origin and number of branches. We dissected 101 upper extremities from 32 male and 20 female cadavers to expose the PAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 11 publications
(10 reference statements)
0
11
1
Order By: Relevance
“…This is consistent with two previous studies that found the PABCN emerged from the hiatus at 70 mm and 66 mm from the lateral epicondyle respectively. 9,12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with two previous studies that found the PABCN emerged from the hiatus at 70 mm and 66 mm from the lateral epicondyle respectively. 9,12…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with two previous studies that found the PABCN emerged from the hiatus at 70 mm and 66 mm from the lateral epicondyle respectively. 9,12 Previous authors have reported the ability of ultrasound to identify peripheral nerves. [13][14][15] In the upper limb, high-frequency ultrasound has been used to identify and block the MABCN and LABCN.…”
Section: Discussionmentioning
confidence: 99%
“…present study is morphologically similar to that of type 2 of Venieratos et al, 10 but with two important differences: (1) after the anastomosis with the MN, the MCN does not emit its terminal branch, the LCNF, (2) we suggest that the part of the cutaneous innervation of the forearm that is made by the LCNF is supplied by the posterior antebrachial cutaneous nerve (PACN), a branch of the radial nerve, providing sensory innervation to the skin of the posterior forearm. 14 Matzi et al 15 reported that, after the separation from the radial nerve, the PACN emerged from the lateral intermuscular septum (LIMS), and immediately pierced the deep fascia after emerging from the LIMS. 16 More distally, its main trunk and branches course in the subcutaneous layer to the posterior forearm, as far as the wrist.…”
Section: Cerda 2014 30mentioning
confidence: 99%
“…14 Data regarding its anatomy remain insufficient, especially regarding its origin and number of branches. 14 The anastomotic variability between the MCN and the MN described in the literature suggest that these anastomoses may be attributed to ontogenetic and phylogenetic factors that influence the formation mechanism of muscles and nerves of the upper limbs during embryonic life. 17,18 Significant variations in nerve patterns may be a result of altered signaling between mesenchymal cells and neuronal growth cones.…”
Section: Cerda 2014 30mentioning
confidence: 99%
See 1 more Smart Citation